Understanding Poverty and Social Assistance Distribution: A Multidimensional Approach to Rural Poverty in Indonesia - Hakim, Lukman; Kolopaking, Lala M.; Sjaf, Sofyan; Kinseng, Rilus A. (Universitas Muhammadiyah Yogyakarta, 2025)
Poverty is a crucial issue to address in sustainable development, particularly in rural areas. Despite the government’s attempts to intervene through social assistance programs for people experiencing poverty, poverty remains unabated. This study investigated rural poverty in Indonesia using three major analytical frameworks: the World Bank’s poverty line, the BPS-Statistics Indonesia poverty line, and Indonesia’s Law on Poverty Alleviation. Employing a quantitative approach with 289 respondents across three villages in West Java, the study integrated income-based and access-based indicators to construct six categories of poverty: (1) extreme poverty, (2) vulnerable to extreme poverty, (3) non-monetary poverty, (4) regional poverty, (5) vulnerable to regional poverty, and (6) non-poor. The findings revealed that 35.99% of social assistance distribution was misallocated, with 12.46% of poor people excluded and 23.53% of non-poor beneficiaries incorrectly included. By introducing a refined, empirically grounded classification system, this research enhanced multidimensional poverty measurement and advocated for systemic reforms in data collection to improve the accuracy and targeting of rural social assistance programs.